Lactation support, prevention and treatment of hypogalactia - A. F. Kiosov (Лечащий Врач)
The article presents data on the stimulation and support of lactation after childbirth in lactating women and a review of the known drug and non-drug lactogonic agents. The most widely known lactogonic drugs are metoclopramide and domperidone. However, they have significant limitations for use due to serious side effects. Non-pharmacological lactogonic agents include lactogonic herbs and products of plant origin.